(untitled) (Journal of Chemical Engineering, 2014)
In this study, a cost effective, simple, environment friendly way of fermentable reducing sugar production from rice straw has been carried out by using naturally grown raw wood rotting enzyme. The rotten bark of three trees was collected as the source of enzyme, called enzyme strain. The yield of reducing sugar from rice straw by enzyme strain at various operating condition was studied. A kinetic model expression has been developed for the enzymatic hydrolysis process based on the Michaelis Mentens approach. Comparison between the experimental data and theoretical data predicted from the rate model render sound accord with a mean deviation of about 0.679. Strain collected from the Rain tree (Samanea Saman) showed the maximum production of reducing sugar. The absence of light gives 36.36% higher production than that of the presence of light. The optimum pH is found as 5. Strain concentration at 0.0233g/ml shows the maximum sugar production as 0.09854 mg/ml in 10 days. Substrate concentration at .0143mg/ml gives maximum production of 0 .15991 mg/ml in 16 days. From this study the optimum condition was found as 0.157 mg/ml fermentable reducing sugar in 11 days. This study provides an alternative and attractive cost effective source of fermentable sugar which can be further converted to valuable product such as bio-ethanol to meet the worlds increasing energy demand. DOI: http://dx.doi.org/10.3329/jce.v28i1.18108 Journal of Chemical Engineering, Vol. 28, No. 1, December 2013: 32-35